Coordinating Supply Chain Management Strategy with Corporate Strategy - Veselko, Gregor; Jakomin, Igor (Promet - Traffic&Transportation, 2008)
The background of the paper is the substantial developmentin international business with special regard to globalizationand business internationalization going on over the pastfew years. The latest has put many companies facing big challengesand devised methods for their sustainable incorporationin global supply chains. The purpose of the paper is to help outthe reader and explain the major effects the globalization andbusiness internationalization have on business strategy formationand its implementation. Coordinating business strategyhas become one of the key elements for international competitiveattractiveness. The final goal of the paper is to make a logicalconnection between supply chain management strategy andcorporate strategy. The results of the paper confirm the basicimplication that the supply chain management strategy andc01porate strategy must be coordinated and implemented accordingto certain requirements, considering that the sustainablecorporate strategy is the logical consequence of a thoroughlyexamined and properly understood supply chain managementstrategy.